Modern Stochastic Gaussian Models and Applications to Finance - Almani, Hamidreza Maleki (Vaasan yliopisto, 2024)
This thesis is an attempt to develop the modern stochastic processes and their associated models as well as their applications, particularly to finance. The results of this thesis are published in four articles. The first and the second articles deal with extended Gaussian processes, with mixed long-memory behaviour (which is widely used in finance). In the first article, we introduced and analyzed the multi-mixed fractional Brownian motion (mmfBm) and its associated Ornstein–Uhlenbeck (OU) process, and in the second one, we investigated a parameter estimation for the OU process based on the generalized method of moments (GMM). In the third article, we considered the prediction of Gaussian Volterra processes with jumps. Finally, by using these results in our fourth article, we investigated the conditional mean hedging and the conditional least square strategies in a Black-Scholes model with jumps and with transaction costs.

Tämä väitöskirja tarkastelee moderneja stokastisia prosesseja ja stokastisia malleja ja niiden sovelluksia erityisesti rahoituksessa. Tulokset on julkaistu neljässä artikkelissa. Ensimmäinen ja toinen artikkeleista käsittelevät laajennettuja gaussisia prosesseja, joilla on sekoitettu pitkän aikavälin riippuvuus (tällaisia malleja käytetään laajasti rahoituksessa). Ensimmäisessä artikkelissa esittelemme ja analysoimme monisekoitettua fraktionalista Brownin liikettä (mmfBm) ja siihen liittyvää Ornstein-Uhlenbeck-prosessia (OU), ja toisessa artikkelissa tarkastelemme parametrien estimointia OU-prosessille yleistettyjen momenttien menetelmällä (GMM). Kolmannessa artikkelissa tarkastelemme ennustamista gaussisille Volterra-prosesseille, joilla on hyppyjä. Lopuksi neljännessä artikkelissa tarkastelemme ehdollista keskisuojausta Black-Scholes-mallissa jossa on hyppyjä ja transaktiokuluja.
Keywords: mathematics; stochastic processes; Gaussian processes; mathematical models; motion; probability calculation; econometrics; financial markets; fi=Matematiikka|en=Mathematics|